THE EFFECT OF OODEVON GONAD MATURATIONOF BETOK (Anabas testudineus Bloch) - Rifqa Rahmi; Netti Aryani; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT The aim of this research was to determine the effect of oodev on gonad maturation of Betok (Anabas testudineus Bloch). This research was conducted from December 2018 - February 2019 at Fish Hatchery and Breeding Laboratory, Fisheries and Marine Science Faculty Riau University. The method used is an experimental method with a Completely RandomizedDesign (CRD)with four treatments and three replications.The treatment were P1 (Oodev 0 ml/kg body weight), P2 (Oodev 0,3 ml/kg body weight), P3 (Oodev 0,5 ml/kg body weight), and P4 (Oodev 0,7 ml/kg body weight).The result showed that Oodev on gonad maturationof P4 (Oodev 0,7 ml/kg body weight) was the heighest with gonad maturation, latency period 5.03 hours, number off eggsstripping 200 egg/g broodstock, ovisomatic index 23,67%, increase of diameter egg 0,167mm, increase of eggs maturation 11%, fertilization rate 91,66%, hatching rate 97,07%, and survival rate 97,07%. The water quality parameters during research was in optimal range temperature 25-28°C, pH 6and dissolved oxygen 3,77-5,20 mg/l. Keywords :Anabas testudineus Bloch, Oodev, Gonad Maturity